2020
DOI: 10.3390/antibiotics9090529
|View full text |Cite
|
Sign up to set email alerts
|

Medical-Grade Honey Kills Antibiotic-Resistant Bacteria and Prevents Amputation in Diabetics with Infected Ulcers: A Prospective Case Series

Abstract: Diabetic ulcers are at risk of becoming chronic and infected, as diabetics have hampered vascular structures, limiting oxygen and nutrient supply. These wounds can lead to pain, malodor, functional problems, and amputation. The current rise in antibiotic resistance demands for complementary therapies. Medical-grade honey (MGH) forms an attractive option because of its antimicrobial and pro-healing properties. We aim to show the beneficial effects of MGH in infected diabetic ulcers. We present six patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(75 citation statements)
references
References 29 publications
7
66
0
Order By: Relevance
“…Even at 6.25-fold dilution, this medical-grade honey formulation induced a more than 1-log reduction in all Candida strains. This medical-grade honey formulation effectively treats infected human wounds with (multiresistant) bacteria [ 16 ] and the canine otitis externa [ 26 ]. Therefore L-Mesitran ® Soft is a potential candidate for the treatment of wounds and skin colonized with C. auris and other Candida species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even at 6.25-fold dilution, this medical-grade honey formulation induced a more than 1-log reduction in all Candida strains. This medical-grade honey formulation effectively treats infected human wounds with (multiresistant) bacteria [ 16 ] and the canine otitis externa [ 26 ]. Therefore L-Mesitran ® Soft is a potential candidate for the treatment of wounds and skin colonized with C. auris and other Candida species.…”
Section: Discussionmentioning
confidence: 99%
“…CE- and FDA-approved L-Mesitran ® Soft [ 16 , 19 ] (formulation containing 40% medical-grade honey, hypoallergenic lanolin, propylene glycol, PEG 4000, and vitamins C and E), pure medical-grade honey following strict guidelines [ 10 ] (honey component of ® L-Mesitran ® Soft, Brazilian blossom honey) and unprocessed (non-sterilized) local honey (provided by local beekeeper from Mook, the Netherlands) were included in this study. These compounds were suspended in 1× RPMI 1640 medium to reach final concentrations of 16% and 40% ( v / v ) after the addition of Candida suspensions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in vivo studies demonstrated that this type of honey was able to reduce the microbial colonization of skin of healthy volunteers 100-fold [107]. More recently, L-Mesitran products, formulated with medical-grade honey, demonstrated in vitro their activity against MRSA [99], and in vivo their promising applicability to treat chronic diabetic ulcers, preventing amputations derived from antibiotic-resistant infections [108].…”
Section: Honey Against Antibiotic-resistant Bacteriamentioning
confidence: 99%
“… 47 Furthermore, Nair et al (2020) reported on the successful healing of diabetic foot ulcers (six patients) following topical application of L-Mesitran. 48 The wounds had previously failed to respond to a range of other treatments including antibiotics. Another case study reported on successful eradication of infection in an MRSA infected titanium mesh in an incisional hernia in a 70-year-old female patient treated with L-Mesitran.…”
Section: Resultsmentioning
confidence: 99%